Feasibility study on reusing Sewerage Treatment Plant (STP) effluent in aquaponics system - Soong, Hui Ying (2017)
Malaysia spends millions of ringgits every year to treat wastewater. At the end of the day, all the treated wastewater is wasted, discharged into an open water system. Treated wastewater contains a high amount of useful nutrient that is suitable for agriculture but it also contains a certain amount of heavy metals which can be removed naturally by plants through the process of phytoremediation. The world is also facing another issue which is the limited amount of unpolluted water available. Aquaponics is a system that can potentially address the mentioned issues. This research serves as a feasibility study on the use of STP effluent in an aquaponics system. The main aim of this research is to prove that STP effluent added aquaponics system is safe in practice and able to produce food that is safe to be consumed. The research was divided into three phases, top up of effluent into system biweekly, top up of effluent every day for two weeks and testing of fish and plant samples for heavy metal content. Water samples were taken biweekly for the first part to ensure that the water is in optimum condition. Water sample was also taken for the second phase but only at the beginning and end, to detect any major changes in water parameters. Temperature and pH values were taken every day for both parts of the research. In the third phase, fish and plant samples were taken for heavy metal tests and compared with the amount of heavy metal content allowed by the Malaysian Food Act 1983. From the results, it was shown that adding of effluent will not affect the system in short and long term because the water parameters before and after of every top up are affected insignificantly and food produced from the system is safe where heavy metal level is below the maximum permitted amount.